Les adventices en riziculture en Afrique de l'Ouest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Les adventices, ou mauvaises herbes, sont considérées comme la contrainte biologique la plus importante de la production de riz. Pour aider